2013
DOI: 10.1021/jo401170y
|View full text |Cite
|
Sign up to set email alerts
|

A Constrained Tricyclic Nucleic Acid Analogue of α-l-LNA: Investigating the Effects of Dual Conformational Restriction on Duplex Thermal Stability

Abstract: A constrained tricyclic analogue of α-L-LNA (2), which contains dual modes of conformational restriction about the ribose sugar moiety, has been synthesized and characterized by X-ray crystallography. Thermal denaturation experiments of oligonucleotide sequences containing this tricyclic α-L-LNA analogue (α-L-TriNA 2, 5) indicate that this modification is moderately stabilizing when paired with complementary DNA and RNA, but less stabilizing than both α-L-LNA (2) and α-L-TriNA 1 (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, and except for the original Imanishi report, previous approaches to the synthesis of LNA-related nucleosides utilized appropriate carbohydrate molecules as starting materials. In particular, this strategy allowed the stereocontrolled introduction of a given nucleobase to give the β- d -4′-branched ribonucleoside, which was then elaborated further to incorporate the 2′,4′-oxamethylene bridge via an S N 2 displacement reaction. Inspired by the Imanishi synthesis of LNA starting with uridine, we envisaged that the 2′,4′-ether bridge in ( S )-cEt-BNA can be formed via S N 2 displacement of an appropriate leaving group by the 2′ alcohol of nucleoside A (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, and except for the original Imanishi report, previous approaches to the synthesis of LNA-related nucleosides utilized appropriate carbohydrate molecules as starting materials. In particular, this strategy allowed the stereocontrolled introduction of a given nucleobase to give the β- d -4′-branched ribonucleoside, which was then elaborated further to incorporate the 2′,4′-oxamethylene bridge via an S N 2 displacement reaction. Inspired by the Imanishi synthesis of LNA starting with uridine, we envisaged that the 2′,4′-ether bridge in ( S )-cEt-BNA can be formed via S N 2 displacement of an appropriate leaving group by the 2′ alcohol of nucleoside A (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the Imanishi synthesis of LNA starting with uridine, we envisaged that the 2′,4′-ether bridge in ( S )-cEt-BNA can be formed via S N 2 displacement of an appropriate leaving group by the 2′ alcohol of nucleoside A (Scheme ). This approach has been successfully applied in the synthesis of complex nucleosides bearing the protected 3′-OH. , In the case of the diol group in A , we would face a 4-exotet vs 5-exotet cyclization both favored by Baldwin’s rules, hoping that the formation of the four-membered ring oxetane to be less favored due to ring strain in the [2.1.1]dioxabicycloheptane core structure. With this strategy in mind, the stereoselective addition of a methyl group to the corresponding aldehyde to obtain the ( R )-alcohol B required particular attention.…”
Section: Resultsmentioning
confidence: 99%
“… One dual constrained analogue based on the α-L-LNA scaffold indeed showed enhanced RNA affinity, while a second analogue was slightly destabilizing relative to α-L-LNA (Figure ). In the β-D-LNA series, one dual constrained analogue showed LNA-like binding affinity for RNA while a second analogue was less stabilizing . Examination of structural models suggested that the six-membered carbocyclic may experience tighter contact with the sugar–phosphate backbone in analogues which showed lower affinity in both series …”
Section: Dual Constrained Nucleic Acid Analoguesmentioning
confidence: 99%
“…The development of novel conformationally restricted nucleotides is a vibrant area of research. , Efforts are driven by the interesting properties of oligodeoxyribonucleotides (ONs) modified with classic examples of conformationally restricted nucleotides such as homo-DNA, hexitol nucleic acid (HNA), cyclohexane nucleic acid (CeNA), bicyclo DNA, tricyclo DNA, or locked nucleic acid (LNA), , which is also known as bridged nucleic acid (BNA) . ONs comprising these building blocks display high affinity toward complementary DNA/RNA often due to reduced entropic binding penalties and are accordingly in high demand for a wide range of nucleic acid targeting applications in molecular biology, biotechnology, and pharmaceutical science .…”
Section: Introductionmentioning
confidence: 99%
“…Many analogues of LNA have been synthesized with the aim of further improving the binding affinity/specificity, enzymatic stability and pharmokinetic characteristics of LNA. ,, The vast majority of these efforts have focused on modifying the oxymethylene bridge spanning the C2′/C4′-positions and/or introducing minor-groove-oriented substituents on the bridge. These structural perturbations have resulted in improved enzymatic stability and altered biodistribution and/or toxicity profiles but have generally not resulted in major improvements in binding affinity and specificity.…”
Section: Introductionmentioning
confidence: 99%